2014
DOI: 10.1038/srep06912
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid-based Hydroxyapatite Composite Scaffolds Enhance Calvarial Regeneration

Abstract: Citric acid-based polymer/hydroxyapatite composites (CABP-HAs) are a novel class of biomimetic composites that have recently attracted significant attention in tissue engineering. The objective of this study was to compare the efficacy of using two different CABP-HAs, poly (1,8-octanediol citrate)-click-HA (POC-Click-HA) and crosslinked urethane-doped polyester-HA (CUPE-HA) as an alternative to autologous tissue grafts in the repair of skeletal defects. CABP-HA disc-shaped scaffolds (65 wt.-% HA with 70% poros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 51 publications
1
64
0
Order By: Relevance
“…Radiological evaluation has been used by several researchers to examine the progress of bone healing in clinical and animal experiments [40,41]. The current study findings support the previous reports suggesting that the use of BRMs promotes bone defect healing.…”
Section: Radiological Assessmentsupporting
confidence: 88%
See 1 more Smart Citation
“…Radiological evaluation has been used by several researchers to examine the progress of bone healing in clinical and animal experiments [40,41]. The current study findings support the previous reports suggesting that the use of BRMs promotes bone defect healing.…”
Section: Radiological Assessmentsupporting
confidence: 88%
“…On the other hand, the Control group had significantly lower bone density than Bio Oss and β-TCP only at one-month post GBR, while the bone density difference across the groups at two-month post GBR was not statistically significant. Sun et al [40] however, reported an enhanced bone mineral density, trabecular thickness, and angiogenesis when comparing regenerative defects to the control groups at 1 st , 3…”
Section: Radiological Assessmentmentioning
confidence: 94%
“…Recently, HA is being investigated for use in various nanomaterials for its potential biocompatibility as well as osteoinductive properties [3133]. Synthetic hydroxyapatite (HAp) is essentially identical to naturally occurring HA and has therefore become a commonly investigated biomaterial for use in skeletal, orthopedic, and dental repair, in part, by enhancing cell attachment, proliferation, and mineral formation [3437]. Nano-HAp is now being investigated as a biomaterial to be used; directly as a therapeutic, a major component of bone graft substitutes, and an implant coating to improve biocompatibility and skeletal repair (reviewed in [36, 38–40]).…”
Section: Introductionmentioning
confidence: 99%
“…CA has been shown to exhibit osteoinductivity by enhancing alkaline phosphatase (ALP) and osterix (OSX) gene expression from in vitro studies [22]. Another study on effect of citric acid-based hydroxyapatite composite on stem cells reported that citrate may have considerable effect on bone development for orthopedic biomaterials [23]. Hence, it can be concluded that CA present in CPC may enhance the bone formation.…”
Section: Resultsmentioning
confidence: 99%